A biomarker panel predicts progression of Barrett's esophagus to esophageal adenocarcinoma. Issue 1 (28th November 2018) - Duits, L C; Lao-Sirieix, P; Wolf, W A; O'Donovan, M; Galeano-Dalmau, N; Meijer, S L; Offerhaus, G J A; Redman, J; Crawte, J; Zeki, S; Pouw, R E; Chak, A; et al.
Summary: Progression from Barrett's esophagus (BE) to esophageal adenocarcinoma (EAC) is uncommon but the consequences are serious. Predictors of progression are essential to optimize resource utilization. This study assessed the utility of a promising panel of biomarkers applicable to routine paraffin embedded biopsies (FFPE) to predict progression of BE to EAC in a large population-based, nested case-control study. We utilized the Amsterdam-based ReBus nested case-control cohort. BE patients who progressed to high-grade dysplasia (HGD)/EAC ( n = 130) and BE patients who never progressed ( n = 130) were matched on age, sex, length of the BE segment, and duration of endoscopic surveillance. All progressors had minimum 2 years of endoscopic surveillance without HGD/EAC to exclude prevalent neoplasia. We assessed abnormal DNA content, p53, Cyclin A, and Aspergillus oryzae lectin (AOL) in FFPE sections. We performed conditional logistic regression analysis to estimate odds ratio (OR) of progression based on biomarker status. Expert LGD (OR, 8.3; 95% CI, 1.7–41.0), AOL (3 vs. 0 epithelial compartments abnormal; OR, 3.6; 95% CI, 1.2–10.6) and p53 (OR, 2.3; 95% CI, 1.2–4.6) were independently associated with neoplastic progression. Cyclin A did not predict progression and DNA ploidy analysis by image cytometry was unsuccessful in the majority of cases, both were excluded from the multivariate analysis. The multivariable biomarker model had an area under the receiver operating characteristic curve of 0.73. Expert LGD, AOL, and p53 independently predict neoplastic progression in BE patients and are applicable to routine practice. These biomarkers can aid in selecting patients for endoscopic ablation or more intensive surveillance.